1-Alkyl-1H-Benzimidazolium Sulfonates as Non-Competitive Inhibitors of Polyphenol Oxidase - Ergun, Adem; Cikrikci, Kubra; Gencer, Nahit; Arslan, Oktay; Uslu, Harun; Goktas, Bunyamin; Karatas, Mert Olgun (Wiley, 2026)
Polyphenol oxidase (PPO) has been the subject of many inhibition studies due to its presence in many species, causing enzymatic browning in fruits and vegetables, and its pigmentation role in mammalian species. In the present study, the inhibitory properties of twelve 1-alkyl-1H-benzimidazolium sulfonates and two 1-alkyl-1H-benzimidazolium iodides on PPO activity have been investigated. The PPO enzyme was purified from banana using Sepharose 4B-tyrosine-p-aminobenzoic acid affinity gel chromatography. The effects of 14 different synthesized benzimidazole derivatives on the PPO enzyme were investigated, and they were found to significantly inhibit the enzyme in question. When ADME predictions were examined, it was seen that all compounds that include methylbenzenesulfonate structure showed good pharmacokinetic properties; only compounds 3a and 3b, which contain iodide, violated the Ghose rules. These compounds, which were effective at low concentrations, may serve as promising lead molecules for the development of PPO inhibitors with potential applications in food preservation, cosmetic formulations, and pharmaceutical research, pending further in vivo and formulation-based studies.
Keywords: benzimidazole; benzimidazolium salts; inhibitors; non-competitive inhibition; PPO inhibition